Bibliografia przekładów literatury macedońskiej w Polsce i polskiej w Macedonii (lata 2007—2013) — komentarz literaturoznawczy - Miodyński, Lech (Przekłady Literatur Słowiańskich, 2014)
The Bibliography of Literary Translations 2007—2013 (Poland — Macedonia). A Commentary In the study an attention is drawn to the problems concerning the cultural and artistic representativeness of the choices of the translated literary texts, that are made by actors of both sides of the linguistic communities: Polish and Macedonian. An overview of such choices connects the relationships with social backgrounds of the cultural elites and with the continuity of the both literary traditions. The comparison has proved that the Macedonian translations, starting from the 70s of the 20th century, systematically present important Polish literary texts, reflecting our national canon. On the other hand, Polish translators treat their contacts with the contemporary Macedonian poetry, prose and drama incidentally, that results in ad hoc motivations, both institutional and personal. Key words: Macedonian literature, Polish literature, translation, choice representativeness, cultural restrictions.